Mixture of trypsin, chymotrypsin and papain reduces formation of metastases and extends survival time of C57Bl6 mice with syngeneic melanoma B16 - Wald, M; Olejár, T; Sebková, V; Zadinová, M; Boubelík, M; Poucková, P (Cancer chemotherapy and pharmacology, 2001)
PURPOSE: The aim of the present study was to investigate the effect of a mixture of proteolytic enzymes (comprising trypsin, chymotrypsin and papain) on the metastatic model of syngeneic melanoma B16. METHODS: 140 C57B16 mice were divided into two control and two "treated" groups. Control groups received saline rectally, twice a day starting 24 h after intracutaneous transplantation (C1) or from the time point of the primary B16 melanoma extirpation (C2), respectively. "Treated" groups were rectally administered a mixture of 0.2 mg trypsin, 0.5 mg papain, and 0.2 mg chymotrypsin twice daily starting 24 h after transplantation (E1) or after extirpation of the tumor (E2), respectively. Survival of mice and B16 melanoma generalization were observed for a period of 100 days. Immunological evaluation of B16 melanoma cells in the ascites was accomplished. CD44, CD54 and CD106 cells were measured by flow cytometry. RESULTS: Administration of proteolytic enzymes to mice inhibited the growth of primary tumors, and tumor recurrences were less numerous. Importantly, metastasis was considerably curtailed both in the vicinity of the primary tumor and at distant locales. These findings correlated with a decreased expression of CD44 and CD54 molecules in tumors exposed to proteolytic enzymes in vivo. CONCLUSIONS: Our data suggest that serine and cysteine proteinases suppress B16 melanoma, and restrict its metastatic dissemination in C57B16 mice.
Keywords: chymotrypsin; nádory plic; Cell Division; Lung Neoplasms; Hyaluronan Receptors; aplikace rektální; Immunoglobulins; fixní kombinace léků; papain; Female; Antigens, Surface; endopeptidasy; Antineoplastic Agents; Endopeptidases; antigeny povrchové; Chymotrypsin; zvířata; myši; antigeny CD44; myši inbrední C57BL; Mice; Trypsin; ženské pohlaví; mezibuněčná adhezivní molekula-1; Mice, Inbred C57BL; protinádorové látky; Animals; Intercellular Adhesion Molecule-1; Melanoma, Experimental; trypsin; melanom experimentální; Drug Combinations; Administration, Rectal; imunoglobuliny; Papain; buněčné dělení